Spatial distribution, bioavailability, and toxicity of metals in surface sediments of tropical reservoirs, Brazil - Frascareli, Daniele [UNESP]; Cardoso-Silva, Sheila [UNESP]; de Oliveira Soares-Silva Mizael, Juliana [UNESP]; Rosa, André Henrique [UNESP]; Pompêo, Marcelo Luiz Martins; López-Doval, Julio Cesar; Moschini-Carlos, Viviane [UNESP] (Springer Nature, 2018)
Depending on the environmental conditions, surface sediments can retain all the contaminants present and provide a record of the anthropic activities affecting the aquatic environment. In order to analyze the impacts on reservoirs, surface sediments were collected in three characteristic regions (riverine, transitional, and limnetic zones) of seven reservoirs in São Paulo State, Brazil. Analyses were made of grain size, organic matter (OM), total phosphorus (TP), and total nitrogen (TN). Inductively coupled plasma-atomic emission spectroscopy (ICP-AES) was used to determine pseudo-total and bioavailable metals (Cu, Cd, Cr, Ni, Pb, Zn, Mn, Fe, and Al). A Horiba probe was used to measure dissolved oxygen (DO), pH, redox potential (ORP), and temperature (Temp) in the bottom water. The data were analyzed using multivariate statistics. Enrichment factors (EF), pollution load index values (PLI), and background values (BG) were also determined in order to evaluate the potential toxicity. Intra-reservoir and inter-reservoir spatial heterogeneity (p OpenSPiltSPi 0.05) were observed using two-way analysis of similarities. Principal component analysis indicated greater influence of metals in the Barra Bonita, Salto Grande, and Rio Grande reservoirs, corroborating the PLI, EF, and BG data. Bioavailable Cu was found in the Rio Grande reservoir, possibly associated with copper sulfate used to control algal blooms, while bioavailable Ni in the Barra Bonita reservoir was attributed to the presence of industrial wastes and natural geology. The bottom water conditions indicated that the metals remained in insoluble forms.
Keywords: Metals; Surface sediment; Tropical reservoirs